Pengembangan Media Rumah Pelajar Pancasila dalam Mengenalkan Keberagaman pada Anak Usia Dini di Tk Permata Sunnah Kecamatan Kota Selatan Kota Gorontalo - Putri Regina Cahyani; Pupung Puspa Ardini; Yenti Juniarti (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The lack of instructional media usage in classroom teaching and learning activities serves as the primary problem in this study. This research aims to develop Rumah Pelajar Pancasila media to introduce diversity to early childhood students at TK Permata Sunnah Kindergarten, Kota Selatan District, Gorontalo City. The study employed a Research and Development (R&D) approach using the ADIDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of the study indicated that Rumah Pelajar Pancasila media is highly feasible. Validation by subject matter experts yielded a feasibility score of 96.36% (Highly Feasible), while validation by media experts produced a score of 96.25% (Highly Feasible). The pilot test with teachers received an 80% feasibility score (Feasible), and testing with children resulted in a score of 4 (Feasible). In the large-group trial, teachers rated the media with 100% feasibility (Highly Feasible), and children provided a score of 5 (Highly Feasible).In conclusion, the development of Rumah Pelajar Pancasila media is effective in introducing diversity to young children.